PENGELOLAAN PEMBELAJARAN PRAKTEK AKUNTANSI MENGGUNAKAN MODEL KONTEKTUAL UNTUK MENINGKATKAN KOMPETENSI SISWA PADA MATA PELAJARAN AKUNTANSI DI KELAS XI IPS 1 SMA NEGERI 7 BOGOR - Tuti Herawati (Jurnal Ilmiah Econosains, 2010)
ABSTRACTThis research aim to develop management of study of practice of accountancy applies contextual model which can be exploited in process of study to increase student interest at accountancy subject. This research done in class XI IPS1 SMAN 7 Bogor applies Classroom Action Research contextual model consisted of two cycles to refer to Model Kurt Lewin its (the activity covering: (1) planning, (2) action of execution, (3) observation, and ( 4) reflection. Based on finding result of research indicates that: (1) In executing management of study of practice of teacher accountancy have been able to apply contextual model to increase attainment of student learning interest; this thing is visible result of first cycle interest test result has not shown Criteria Complete Minimal (KKM), while second cycle interest test result hardly gladdens because result of acquirement above indicator Criteria Complete Minimal (KKM) what specified. (2) Approach study plan of contextual correctly can be exploited in class XI IPS SMAN 7 that is management of study of practice of accountancy applies contextual model and student spread sheet as study guidance referring to study indicator. (3) Study activity is done not only in class but for study activity of accountancy computer can apply computer laboratory. (4) Percentage of enthusiastic and involvement of student learning at showing second cycle is improvement, this thing is a real good result mean attention of student to study and can entangle itself in study.Keywords: Contextual Teaching and Learning (CTL), Student Competence.